Effects of reservoir cascades on diversity, distribution, and abundance of fish assemblages in three Neotropical basins - Ganassin M.J.M. (2021)
© 2021 Elsevier B.V.River systems are characterized by the existence of longitudinal processes structuring fish assemblages. However, the construction of dams, many of them built in cascades, are disrupting these processes worldwide. Here, we analyzed the fish assemblages across reservoir cascades in three Brazilian river basins (Iguaçu, Paranapanema, and São Francisco) to identify whether there is a spatial convergent pattern and to infer the mechanisms structuring metacommunities in these Neotropical rivers. Linear models were used to assess the effect of reservoir cascades, and the associated morphological, spatial and environmental variables, on the species richness and diversity along them. We analyzed if reservoir cascades produce similar species distribution patterns using the elements of metacommunity structure framework and beta diversity and its components. Finally, super-organizing maps were used to find common trends in species abundances and the environmental, morphological, and spatial variables along cascades. The negative relationship between species richness and diversity and the position in the cascade indicated diversity declines along cascades. However, the resulting metacommunities varied in each river basin. They conformed a quasi-Gleasonian structure, a Clementsian structure, and a nested structure with stochastic species loss in the Iguaçu, Paranapanema, and São Francisco River basins, respectively. Generally, total beta-diversity (βsor) and species turnover (βsim) between pairs of reservoirs increased along reservoir cascades, especially at the downstream end, whereas nestedness (βsne) depicted distinct trends in each river basin. By contrast, there were general decreases in species abundances along cascades, especially downstream the fourth reservoir, with very few species benefiting from such situation. In general, species present in the downstream reservoirs were subsets of the species present in the upstream reservoirs (particularly in the São Francisco River Basin), while some had singular responses to the environmental gradient and appeared or disappeared at random. Although the cascade has an effect on fish assemblages, reservoir characteristics and operation also influence them. Our study highlights the impact of such structures and shows general patterns of fish assemblages that should help to mitigate the resulting ecological impacts and assist the process of infrastructure planning.